The Jewish Cardinal = Le métis de Dieu [videorecording (DVD)] - Duran Cohen, Ilan; Lucas, Laurent; Recoing, Aurélien, 1958-; Dana, Audrey, 1979-; Greggory, Pascal, 1955- (Film Movement series)
The true story of Jean-Marie Lustiger, the son of Polish-Jewish immigrants, who maintained his cultural identity as a Jew even after converting to Catholicism at a young age, and later joining the priesthood. Quickly rising within the ranks of the Church; Lustiger was appointed Archbishop of Paris by Pope Jean Paul II- and found a new platform to celebrate his dual identity as a Catholic Jew; earning him both friends and enemies from either group. When Carmelite nuns settle down to build a convent within the cursed walls of Auschwitz; Lustiger finds himself a mediator between the two communities - and may be forced at last to choose his side.